2008
DOI: 10.1007/s10646-008-0202-4
|View full text |Cite
|
Sign up to set email alerts
|

Clapper rails as indicators of mercury and PCB bioavailability in a Georgia saltmarsh system

Abstract: Mills, Gary L.; Garvin, N.; Stephens, Warren L. Jr.; Novak, James N.; and Brisbin, I. L. Jr., "Clapper rails as indicators of mercury and PCB bioavailability in a Georgia saltmarsh system" (2008 Abstract Clapper rails (Rallus longirostris) were used as an indicator species of estuarine marsh habitat quality because of their strong site fidelity and predictable diet consisting of mostly benthic organisms. Mercury (Hg) and the polychlorinated biphenyl (PCB) Aroclor 1268 concentrations were determined for sedimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 28 publications
1
33
0
Order By: Relevance
“…Gaines et al (1999Gaines et al ( , 2000 assisted the US Fish and Wildlife Service (USFWS) to document the extent of the post-mitigation damage to wildlife resources, using Clapper Rails as an indicator of ecosystem health. Specifi cally, this research reported that birds had elevated levels of DNA strand-breakage, egg-shells had been weakened, and chicks had neurological damage and bone-structural problems (Cumbee et al 2008;Novak et al 2006;Rodriguez-Navarro et al 2002. Although this research helped the USFWS quantify damage to the ecosystem, it left many unanswered questions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Gaines et al (1999Gaines et al ( , 2000 assisted the US Fish and Wildlife Service (USFWS) to document the extent of the post-mitigation damage to wildlife resources, using Clapper Rails as an indicator of ecosystem health. Specifi cally, this research reported that birds had elevated levels of DNA strand-breakage, egg-shells had been weakened, and chicks had neurological damage and bone-structural problems (Cumbee et al 2008;Novak et al 2006;Rodriguez-Navarro et al 2002. Although this research helped the USFWS quantify damage to the ecosystem, it left many unanswered questions.…”
Section: Introductionmentioning
confidence: 99%
“…Clean-up plans often consider action levels to minimize chronic toxic effects, but fail to regard the broader impacts of long-term exposure to populations. The Clapper Rail population in this study has been used as an indicator population for acute effects (Cumbee et al 2008;Novak et al 2006;Rodriguez-Navarro et al 2002. However, the long-term consequences of this perturbation have not been examined.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is also evidence that they are sensitive to certain habitat conditions, such as water quality, and so may be considered wetland quality indicators , Conway 1995, Cumbee et al 2008. Additionally, we examined the effect of vegetation on Marsh Wren (Cistothorus palustris), Yellow-headed Blackbird, and Virginia Rail separately; these are relatively common species in Iowa wetlands but are experiencing population declines elsewhere , Conway 1995).…”
Section: Vegetation Effects On Marsh Bird Abundancementioning
confidence: 99%